The effectiveness of the developed principal's courses in Babylon Governorate from the point of view of school principals - Al-Janabi, Omar Falah Awad; Al-Sadi, Ameer Mohammed Ali Rasool (Al-Adab Journal, 2021)
The research aimed to identify the effectiveness of the courses of the developed director in Babel governorate from the viewpoint of school principals.For the purpose of verifying the research objective, the following two questions were formulated:How effective are the courses of the developed director in Babel governorate from the viewpoint of school principals?Are there statistically significant differences at the level of significance (0.05) between the responses of the sample members according to the gender variable?To answer these two questions, the descriptive approach was followed because it achieves the aim of the research, as a questionnaire consisting of (20) paragraphs was directed to a sample of government school administrations in the center of Babel Governorate - chosen by the class method - (100) school administrations reached (54) principals and (46) Director.The research found that:1- The extent of effectiveness of the courses of the developed director in Babel governorate from the viewpoint of school principals was (average).2- There were no statistically significant differences at the level of significance (0.05) between the responses of the sample members according to the gender variable.